INTERFERENCE AND INTEGRATION IN BALINESE LANGUAGE - Ferryanti, Ni Putu (Widya Accarya, 2015)
Language takes important role in delivering message or information. Nowadays, many people are interested to learn other languages from other countries, especially English language, in order to be able to communicate with people abroad. Regarding every language has its own characteristics and grammatical rules, thus the interference and integration can be occurred during the language learning process. Related to the development of Balinese Language, the interference and integration from English language and Bahasa could give positive or negative impact for the Balinese people in which these interference and integration is effected in the development of Balinese language itself. Moreover, the existence of those new words, which are resulted from interference and integration, can enrich Balinese language vocabularies which indicating that Balinese language capable to receive the vocabularies development in this globalization era even though it is a traditional language. However, it cannot be denied that it also gives negative impact, because it is worried that the existence of new words in Balinese language vocabularies could cause cultural shifting towards the existence of Balinese language itself. Key Words: Interference, Integration, Balinese Language